2005
DOI: 10.1002/polb.20392
|View full text |Cite
|
Sign up to set email alerts
|

Investigating interactions of biomembranes and alcohols: A multiscale approach

Abstract: We study the interaction of lipid bilayers with short chain alcohols using molecular dynamics on different length scales. We use detailed atomistic modeling and modeling on the length scale where an alcohol is just an amphiphilic dimer. Our strategy is to calibrate a coarse-grained model against the detailed model at selected state points at low alcohol concentration and then perform a wider range of simulations using the coarse-grained model. We get semiquantitative agreement with experiment for the major obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
(79 reference statements)
4
22
0
Order By: Relevance
“…The results shown that ethanol interacts with a POPC membrane primarily via hydrophilic interactions, in particular due to the formation of hydrogen-bonds to the lipid phosphate group. A recent MD investigation has also supported these results and shows that shortchain alcohols exhibit some preference to occupy regions near the upper part of the lipid acyl chains and the phosphatidylcholine headgroups [33,34,61,62]. Additionally, it has been shown that, in a homologous series of aliphatic n-alcohols with an intermediate chain length, an increase in the number of carbon atoms of an alkyl chain (butanol, pentanol and hexanol) results in a gradual decrease in hydrophilic solute-membrane interactions, so that a partitioning process and packing of solute molecules in alcohol/membrane/water systems are driven mainly by hydrophobic forces [63,64].…”
Section: Simulations Of Ternary Cp/membrane/water Systemssupporting
confidence: 50%
See 1 more Smart Citation
“…The results shown that ethanol interacts with a POPC membrane primarily via hydrophilic interactions, in particular due to the formation of hydrogen-bonds to the lipid phosphate group. A recent MD investigation has also supported these results and shows that shortchain alcohols exhibit some preference to occupy regions near the upper part of the lipid acyl chains and the phosphatidylcholine headgroups [33,34,61,62]. Additionally, it has been shown that, in a homologous series of aliphatic n-alcohols with an intermediate chain length, an increase in the number of carbon atoms of an alkyl chain (butanol, pentanol and hexanol) results in a gradual decrease in hydrophilic solute-membrane interactions, so that a partitioning process and packing of solute molecules in alcohol/membrane/water systems are driven mainly by hydrophobic forces [63,64].…”
Section: Simulations Of Ternary Cp/membrane/water Systemssupporting
confidence: 50%
“…Therefore, the influence of the lipid membrane on the microstructure of cryoprotectant solutions is also studied. The MD method is widely employed in studying, with the atomic resolution, interactions and the partitioning behavior of organic solvents with phospholipid bilayers and biomembranes [30][31][32][33][34][35][36]. Knowledge and a deeper understanding of the cryoprotection mechanism would help us with the design of better solvent mixtures to improve the cryopreservation properties and cooling/warming procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a consistent strategy for the development of compatible coarse grained and atomic level force fields is of additional importance for its intended use in multiscale applications. [28][29][30][31] The list of applications of our coarse grained model to date includes vesicle formation and fusion, [32][33][34] lamellar phase transformations, [35][36][37] the structure and dynamics of membraneprotein assemblies, 38,39 the structure of bicelles, 40 the equation of state of monolayers, 41,42 and the effect of various molecules on membranes (butanol, 43 DMSO, 44 dendrimers 45 ). In most of these studies the CG model, sometimes with small changes from the published version, performed well in comparison either to experimental data or to more detailed atomistic models.…”
Section: Introductionmentioning
confidence: 99%
“…37,43 It has been long known that the molecular dynamic (MD) simulations are well suited for detailed analysis of the interaction between lipid bilayers and various chemicals and there are some recent studies reporting on the interaction between lipid bilayers and small nonwater polar molecules. [1][2][3][4][5][6][7]10,12,[17][18][19]21,22,[27][28][29][30][31][32]36,[39][40][41][42][43][44]46 Clearly, a detailed description of these studies is beyond the scope of this communication. Of direct relevance to the current study, Patra et al 30 reported the structural changes of dipalmitoylphosphatidylcholine (DPPC) lipid membranes in the presence of relatively small molar fractions (below 1.0 mol%) of ethanol and methanol in water.…”
Section: Introductionmentioning
confidence: 99%